Regulation of the Ni2+ Content in a Hierarchical Urchin-Like MOF for High-Performance Electrocatalytic Oxygen Evolution - Tang, Yijian; Zheng, Shasha; Xue, Huaiguo; Pang, Huan (Frontiers in Chemistry, 2019)
The exploitation of efficient nonprecious electrocatalysts for the oxygen evolution reaction is extremely important but remains a tremendously challenging. Here, we prepared a series of hierarchical urchin-like bimetallic Ni/Zn metal-organic framework nanomaterials that served as high-performance electrocatalysts, by regulating the Ni2+/Zn2+ ratio and using a facile one-step hydrothermal method for the application of oxygen evolution reaction. The structure of the hierarchical urchin-like microspheres could improve the utilization efficiency of the active species by facilitating the diffusion of gas and reducing the transport resistance of ions due to its features of a large interfacial area and convenient diffusion channels. In addition, we found that the higher the Ni ratio was, the better the electrocatalytic performance of these bimetallic metal-organic framework nanomaterials.